Biotechnology for beginners - Renneberg, Reinhard (Elsevier, 2008)
Biotechnology is the applied science of using living organisms and their by-products for commercial development. It has grown and evolved to such an extent over the past few years that increasing numbers of professionals work in areas directly impacted by it. For the first time, this book offers an exciting and colorful overview of biotechnology for professionals and students in a wide array of the life sciences including: Genetics, Immunology, Biochemistry, Agronomy, Food Science, and Animal Science. This book also appeals to the lay reader without a scientific background who is interested in an entertaining and informative introduction to the key aspects of biotechnology